(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The article deals with interactive methods of teaching English. The purpose of introducing innovative methods of teaching a foreign language into the educational process is not just the accumulation of knowledge and skills, but the constant enrichment of creative experience, the formation of a mechanism for self-organization and self-realization of each student, increasing his/her learning motivation.